Crashworthiness Design and Multiobjective Optimization for Hexagon Honeycomb Structure with Functionally Graded Thickness - Ruixian Qin; Junxian Zhou; Bingzhi Chen (Advances in Materials Science and Engineering)
Higher energy absorption efficiency and better crashworthiness performance are always the key objectives for different energy absorbing structures applied in numerous industries including aerospace, rail equipment transportation, and automotive. In this study, a functionally graded thickness (FGT) design method is introduced in the design of a hexagon honeycomb structure to improve energy absorbing efficiency on the basis of a traditional honeycomb with uniform thickness (UT). The validation of a numerical analysis model for a UT honeycomb under axial loading is implemented by a nonlinear finite element code LS-DYNA (V971). Furthermore, the multiobjective crashworthiness optimization of an FGT honeycomb subjected to axial quasi-static compression is conducted to maximize specific energy absorption (SEA) and minimize peak crashing force (PCF). In addition, three surrogate models, including radial basis function (RBF), response surface method (RSM), and kriging (KRG), are compared in the accuracy of predicting SEA and PCF and capacity for optimization design of FGT honeycomb structure; the Nondominated Sorting Genetic Algorithm (NSGA-II) is applied to obtain the Pareto optimal solutions for the maximum thickness, minimum thickness, and thickness variation gradient exponent of a honeycomb wall. The optimal points obtained by different surrogate models subjected to an SEA value of 18.5 kJ/kg, 20 kJ/kg, 22 kJ/kg, and 24 kJ/kg are validated, and corresponding optimal parameters are compared; RBF and RSM are more suitable in crashworthiness optimization design of the FGT honeycomb structure. It is indicated that the FGT honeycomb with optimal geometrical parameters presents remarkable enhancement and energy absorbing potential compared to the traditional honeycomb structure.